MANAGEMENT OF ZYGOMA FRACTURE DUE TO MOTORCYCLE ACCIDENT WITH OPEN REDUCTION AND INTERNAL FIXATION TECHNIQUE AT RSD GUNUNG JATI CIREBON INDONESIA - Tammama, Tichvy; Aldi Rohimawan, M; Widjanarko, Bambang (Fakultas Kedokteran Gigi Unjani, 2025)
Zygoma fracture is part of midfacial trauma, which is usually caused by contact force, especially due to traffic accidents. Zygoma fracture can be accompanied by damage to soft tissue, teeth, and bone structure around the zygoma. A 20-year-old male patient came to the Emergency Room of RSD Gunung Jati Cirebon Indonesia with complaints of bleeding from the mouth for 8 hours due to a motorcycle accident. The patient was wearing a half-face helmet, and his face was hit the sidewalk. and had no history of being unconscious, nausea, vomiting, nor bleeding from the nose and ears. On examination, the face appeared asymmetrical, accompanied by edema and an abrasion wound on the left cheek, a laceration on the tongue, and avulsion of teeth 33 and 42. The patient underwent a CBCT examination, with the results showing a fracture line on the left zygoma. The patient was treated by performing an Open Reduction Internal Fixation (ORIF) on the fracture and stitching the wound on the tongue. The fracture healed well, chewing and speech function improved, and the face returned to symmetry with good dental occlusion. DOI : 10.54052/jhds.v5n1.p59-68